PERAN KEPEMIMPINAN VISIONER KEPALA SEKOLAH HUBUNGANNYA DENGAN KESIAPAN GURU MENYONGSONG REVOLUSI INDUSTRI 4.0 - Mustiningsih Mustiningsih; Maisyaroh Maisyaroh; Nurul Ulfatin (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2020)
Abstract: The purpose of this research is to find out, (1) the level of visionary role of the principal’s visionary leadership, namely the reconstruction of policies, direction determinants, change agents, spokespersons, and trainers as well as the teacher’s readiness variable to meet the industrial revolution 4.0, (2) the relationship between the role of the principal’s leadership in reconstructing the policy towards teacher readiness, (3) the relationship between the variables determining the direction of the teacher’s readiness, (4) the relationship of the agent of change variables to the teacher’s readiness, (5) the relationship of the speaker variable to the teacher’s readiness, (6) the relationship of the coach’s variable to the teacher’s readiness, ( 7) the relationship between the principal’s leadership role in reconstructing policies, directors, change agents, spokespersons, and trainers simultaneously with teacher readiness. This study uses a quantitative approach in the effective SDN Malang. Data collection techniques with a closed questionnaire, using central tendency analysis and path analysis. Keywords: visionary leadership, teacher readiness, industrial revolution 4.0 Abstrak: Tujuan penelitian untuk mengetahui, (1) tingkat variabel peran kepemimpinan visioner kepala sekolah yakni perekonstruksi kebijakan, penentu arah, agen perubahan, juru bicara, dan pelatih serta variabel kesiapan guru menyongsong revolusi industri 4.0, (2) hubungan peran kepemimpinan kepala sekolah dalam merekonstruksi kebijakan terhadap kesiapan guru, (3) hubungan variabel penentu arah terhadap kesiapan guru, (4) hubungan variabel agen perubahan terhadap kesiapan guru, (5) hubungan variabel juru bicara terhadap kesiapan guru, (6) hubungan variabel pelatih terhadap kesiapan guru, (7) hubungan antara peran kepemimpinan kepala sekolah dalam merekonstruksi kebijakan, penentu arah, agen perubahan, juru bicara, dan pelatih secara simultan dengan kesiapan guru. Penelitian ini menggunakan pendekatan kuantitatif di SDN efektif Kota Malang. Teknik pengumpulan data dengan angket tertutup, menggunakan analisis tendensi sentral dan analisis path. Kata Kunci: kepemimpinan visioner, kesiapan guru, revolusi industri 4.0